2013
DOI: 10.1039/c3fd20160k
|View full text |Cite
|
Sign up to set email alerts
|

A new approach toward transition state spectroscopy

Abstract: 10Chirped-Pulse millimetre-Wave (CPmmW) rotational spectroscopy provides a new class of information about photolysis transition state(s). Measured intensities in rotational spectra determine species-isomervibrational populations, provided that rotational populations can be thermalized. The formation and detection of S 0 vinylidene is discussed in the limits of low and high initial rotational excitation. CPmmW 15 spectra of 193 nm photolysis of Vinyl Cyanide (Acrylonitrile) contain J=0-1 transitions in more tha… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
79
2

Year Published

2014
2014
2018
2018

Publication Types

Select...
6
1
1

Relationship

1
7

Authors

Journals

citations
Cited by 39 publications
(83 citation statements)
references
References 45 publications
2
79
2
Order By: Relevance
“…There is likely to be another efficient neutral HNC production mechanism: C 2 H 3 CN photodissociation. Indeed, Wilhelm et al (2009) detected unambiguously HNC IR emission in their C 2 H 3 CN photodissociation experiment at 193 nm with a HCN/ HNC ratio equal to 3.34 in good agreement with theoretical calculations from Homayoon et al (2011) as well as direct HNC absorption by the Chirped-Pulse millimetre-Wave study of C 2 H 3 CN photodissociation (Prozument et al, 2013). The dissociative recombination reaction of HCNH + is an efficient source of HNC as HCNH + is the main ion in Titan's upper atmosphere and the branching ratio for HNC production is estimated to be close to 30% (Semaniak et al, 2001;Mendes et al, 2012;Barger et al, 2003).…”
Section: Hydrogen Isocyanide (Hnc)supporting
confidence: 77%
See 1 more Smart Citation
“…There is likely to be another efficient neutral HNC production mechanism: C 2 H 3 CN photodissociation. Indeed, Wilhelm et al (2009) detected unambiguously HNC IR emission in their C 2 H 3 CN photodissociation experiment at 193 nm with a HCN/ HNC ratio equal to 3.34 in good agreement with theoretical calculations from Homayoon et al (2011) as well as direct HNC absorption by the Chirped-Pulse millimetre-Wave study of C 2 H 3 CN photodissociation (Prozument et al, 2013). The dissociative recombination reaction of HCNH + is an efficient source of HNC as HCNH + is the main ion in Titan's upper atmosphere and the branching ratio for HNC production is estimated to be close to 30% (Semaniak et al, 2001;Mendes et al, 2012;Barger et al, 2003).…”
Section: Hydrogen Isocyanide (Hnc)supporting
confidence: 77%
“…Nevertheless, the study of Blank et al (1998) has clearly shown the presence of cyanoacetylene as a photofragment so that it is more likely that a four-center transition state dominates the cyanoacetylene elimination channel, in contrast to the observation that a three-center transition state dominates the acetylene elimination channel. A recent study of C 2 H 3 CN photodissociation at 193 nm using Chirped-Pulse millimetre-Wave (Prozument et al, 2013) absorption spectroscopy clearly shows the production of HCN and HNC but without quantifying the relative yields of these two species. The branching ratios used in the present work are estimated, taking into account the various experimental studies.…”
Section: B3 C 2 H 3 Cnmentioning
confidence: 96%
“…Surprisingly, there are only a few examples of millimeter/submillimeter wave spectrometers that have been coupled to lasers [61][62][63][64][65]. A schematic diagram of the experimental setup is shown in Figure 2.…”
Section: Experimental Methodsmentioning
confidence: 99%
“…The advantages of chirped-pulse spectroscopy, namely the combination of broadband excitation, multiplexed heterodyne detection, high resolution, and meaningful relative intensities, have been demonstrated in pure rotation spectra of large and small molecules [24,25]. Distinct from conventional millimeterwave spectroscopy that employs a thermal detector or other indirect detection schemes (typically ion detection), chirped-pulse techniques make it possible to 6 capture an entire spectrum (400,000 50 kHz resolution elements) in a single chirp (20 GHz bandwidth) rather than sequentially, one resolution element at a time.…”
Section: Cpmmw Spectrometermentioning
confidence: 99%